Conditions for mutually profitable partnership of members of agricultural consumer cooperatives - G. A. Arshinov; V. N. Laptev; V. G. Arshinov (Новые технологии)
With the help of mathematical modeling, conditions for the emergence of stable integrated associations of a dairy sub-complex of the AIC in the form of agricultural consumer cooperatives are investigated. Parameters of mutually beneficial cooperation of members of a cooperative are proposed.